Spectral gamma-ray and conventional logs to evaluate hydrocarbon potentiality in Bahareya Formation, Hayat oil field, Northwestern Desert, Egypt - SHAHEEN, Mohamed Ahmed (Contributions to Geophysics and Geodesy, 2025)
Different reservoir parameters (volume of shale, total and effective porosities, water saturation and hydrocarbon saturation) of Bahareya Formation were calculated in Hayat-1 well to determine the lithology of rocks and possibility of hydrocarbon accumulation. The volume of shale percentage along the well ranges from 10 to 40%. Meanwhile the depth ranging from 2020 to 2039 m are occupied by clay deposits, in which the values reach more than 75%. Different new applications using spectral gamma-ray logs, as thorium normalization and radiogenic heat production were applied to determine hydrocarbon accumulation zones and differentiate between source and reservoir rocks. The results of radioactive techniques agree well with the results of reservoir parameters, which were calculated from conventional logs, by a percentage ratio that reach more than 80%.